The legal response to safeguarding local environmental quality. (22nd May 2015) - Jenkins, Victoria
Abstract : Local environmental quality is best understood as a measure of the aesthetic complexion of public space in the urban environment. Anti‐social acts causing damage to the physical environment of local communities have, traditionally, attracted little moral opprobrium; and the role of local authorities in safeguarding local environmental quality has been undervalued. However, this is an issue that has been proven to have a significant impact on the quality of life of local communities, particularly those in deprived neighbourhoods. This paper argues, therefore, that we need to develop a comprehensive legal framework to safeguard local environmental quality in the future. This problem has so far been tackled as nuisance, local environmental crime or anti‐social behaviour. The paper concludes that an approach based on measures to tackle incivility in society is to be preferred; thus, the Anti‐social Behaviour, Crime and Policing Act 2014 will be particularly significant in this regard. However, some amendments to this legislation will be required to ensure its effective application to the problems of local environmental quality. Further measures should also be taken to support citizen participation and education as part of a comprehensive legal framework for safeguarding the local environment.